Fata Morgana : poems - Shepherd, Reginald, 1963-2008 (Pitt poetry series., 2007)
Fata Morgana mingles personal experience, history, mythology, politics, and natural science to explore the relationships of conception and perception, the self finding its way through a physical and social world not of its own making, but changing the world by its presence.